PENGARUH VIDEO ANIMASI TERHADAP PENGETAHUAN TENTANG MASA SUBUR PADA REMAJA PUTERI DI SMAN 8 PEKANBARU - Roza Asnel; Ita Yulinda; Mailiza Cahyani; Busyra Hanim (JOMIS (Journal of Midwifery Science), 2025)
Lack of knowledge about the fertile period in adolescent is related to premarital sex behavior, resulting in Unwanted Pregnancy. Rate of Unwanted Pregnancy in adolescents is quite high, which is 12.5%. It can cause the risk of complications in pregnancy and childbirth. Knowledge can be influenced by the educational media used, where interesting media including animated videos can provide good information interest, compared to print media. The purpose of this study was to determine the effect of the use of animated videos on knowledge about the fertile period in adolescent. This type of research is quantitative with a Quasy Experiment design using a one group pre-test and post-test design. The study population was all 12th grade female students, with a sample size of 74 female students, using a simple random sampling technique. Data analysis was carried out univariately and bivariately using the Wilcoxon test. The results of the study showed that the majority of pre-test knowledge had less knowledge, 47 respondents (63.5%), and the majority of post-test knowledge was good, 70 respondents (94.6%, Lack of knowledge about the fertile period in adolescent girls is related to premarital sex behavior, resulting in Unwanted Pregnancy (KTD). The KTD rate in adolescents is quite high, which is 19.6%. KTD can cause the risk of complications in pregnancy and childbirth. Knowledge can be influenced by the educational media used, where interesting media including animated videos can provide good information interest, compared to print media. The purpose of this study was to determine the effect of the use of animated videos on knowledge about the fertile period in adolescent girls. This type of research is quantitative with a Quasy Experiment design using a one group pre-test and post-test design. The study population was all 12th grade female students, with a sample size of 74 female students, using a simple random sampling technique. Data analysis was carried out univariately and bivariately using the Wilcoxon test. The results of the study obtained the results of the pre-test knowledge of the majority of respondents who had less knowledge 47 respondents (63.5%), and the post-test majority had good knowledge 70 respondents (94.6%), with a P Value = 0.000 <0.05 which means H0 is rejected, so it can be concluded that there is an effect of the use of animated video media on knowledge about fertile periods in adolescents. Recommendations for schools to provide ongoing education using animated videos to improve adolescent knowledge about reproductive health.